2008
DOI: 10.1007/s00253-008-1678-9
|View full text |Cite
|
Sign up to set email alerts
|

Improved PCR method for the creation of saturation mutagenesis libraries in directed evolution: application to difficult-to-amplify templates

Abstract: Saturation mutagenesis constitutes a powerful method in the directed evolution of enzymes. Traditional protocols of whole plasmid amplification such as Stratagene's QuikChange™ sometimes fail when the templates are difficult to amplify. In order to overcome such restrictions, we have devised a simple two-primer, two-stage polymerase chain reaction (PCR) method which constitutes an improvement over existing protocols. In the first stage of the PCR, both the mutagenic primer and the antiprimer that are not compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 42 publications
0
98
0
12
Order By: Relevance
“…For PEGylation experiments, the pTK-SM N100-GFP-V5 (WT) (1) was used to generate a cysteine-free mutant, SM N100 C31S,C46S (C-null) and C46S or C31S mutants (designated 31C and 46C, respectively). The C-null plasmid was used to generate single cysteine mutants with either T3C, T9C, T11C, G18C, S37C, V41C, S43C, S59C, G61C, L65C, S67C, S71C, S83C, or S87C mutations using megaprimer site-directed mutagenesis (11). The pCMV-Insig6xmyc (Insig-myc) (12) plasmid used for differential solubilization assays was a generous gift from Drs Michael S. Brown and Joseph L. Goldstein (University of Texas Southwestern, Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…For PEGylation experiments, the pTK-SM N100-GFP-V5 (WT) (1) was used to generate a cysteine-free mutant, SM N100 C31S,C46S (C-null) and C46S or C31S mutants (designated 31C and 46C, respectively). The C-null plasmid was used to generate single cysteine mutants with either T3C, T9C, T11C, G18C, S37C, V41C, S43C, S59C, G61C, L65C, S67C, S71C, S83C, or S87C mutations using megaprimer site-directed mutagenesis (11). The pCMV-Insig6xmyc (Insig-myc) (12) plasmid used for differential solubilization assays was a generous gift from Drs Michael S. Brown and Joseph L. Goldstein (University of Texas Southwestern, Dallas, TX).…”
Section: Methodsmentioning
confidence: 99%
“…We used megaprimer sitedirected mutagenesis (41) to mutate pTK-SM N100-GFP-V5 and pTK-SM-V5 to generate 49 alanine mutants as indicated in the figures. The pTK-SM N49-GFP-V5 construct was generated previously (8).…”
Section: Cholesterol-regulated Degron Of Squalene Monooxygenase Plasmmentioning
confidence: 99%
“…In the present study we applied a "short-cut" quality control as reported earlier. [28] The quality was checked by performing sequence analyses of pooled plasmids for each library prior to transformation into the expression strain (Experimental Section). The results of such an analysis are shown in Table 1.…”
Section: Generation Of Saturation Mutagenesis Librariesmentioning
confidence: 99%